The "Québécois" Separatist Movement and Ascribed Statuses: Features and Consequences - Havet, José; Dignard, Louise (CIENCIA ergo-sum; Vol. 4 Núm. 1 (1997): CIENCIA ergo-sum (marzo-junio 1997), 2017)
-